2020
DOI: 10.2139/ssrn.3633053
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Labor Market at the Onset of the COVID-19 Crisis

Abstract: for excellent research assistance. We are grateful to Homebase (joinHomebase.com), and particularly Ray Sandza and Andrew Vogeley, for generously providing data. We also thank David Gilbertson for tabulations of Kronos data. Caroline Buckee and Victor Chernozhukov provided extremely valuable comments as discussants. We thank Lucas Finamor for pointing out a coding error in an early version of these analyses. The views expressed herein are those of the authors and do not necessarily reflect the views of the Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
7
32
0
1
Order By: Relevance
“…Consistent with the results of Bartik et al (2020), we find that wage rates have remained unchanged through the COVID shock for workers who retained their jobs. Additionally, changes in employment rates are virtually identical to changes in hours because the extensive margin accounts for the vast majority of hours reductions.…”
Section: Iiic Impacts On Employment Rates and Low-income Workerssupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with the results of Bartik et al (2020), we find that wage rates have remained unchanged through the COVID shock for workers who retained their jobs. Additionally, changes in employment rates are virtually identical to changes in hours because the extensive margin accounts for the vast majority of hours reductions.…”
Section: Iiic Impacts On Employment Rates and Low-income Workerssupporting
confidence: 87%
“…Spending and employment remained well below baseline levels even after reopenings, and in particular did not rise more rapidly in states that reopened earlier relative to comparable states that reopened later. Spending and employment also fell well before state-level shutdowns were implemented, consistent with other recent work examining data on hours of work and movement patterns (Bartik et al 2020, Villas-Boas et al 2020.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The relatively large effect of lockdowns has not yet been found empirically in the United States. For instance, Bartik et al [30] found that the relative impact of lockdowns was smaller, explaining 1/6 of the total fall during the COVID-19 pandemic. Our results show that lockdowns explain half of the effect, both in the raw time series ( Figure 3) and in the main regressions (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in the United States have examined how non-pharmaceutical interventions have impacted unemployment insurance, employment, or store client traffic. Some research suggests that lockdowns explain a small share of the total economic activity decline [22,[30][31][32]. Others [24,33,34] have found that lockdowns play a relevant role in explaining the drop in economic activity.…”
Section: Introductionmentioning
confidence: 99%